Study on Aseismic Characteristics of Tibetan Ancient Timber Structure - Juan Wang (Advances in Materials Science and Engineering, 2017)
Tibetan ancient timber structure has great historical, cultural, artistic, and scientific values. The structural configuration of members such as wall, roof, slab, and timber skeleton with semirigid joints is studied in this paper based on field survey results. The aseismic characteristics of Tibetan ancient timber structure have been summarized and introduced. One of the unique features of the Tibetan ancient timber structure is its special beam-column joint which has a semirigid behavior. Numerical simulations of a typical 3-storey structural unit in the Potala Palace are studied. The acceleration responses of the structure under the action of El-Centro seismic waves are studied. Results show that the arrangement of the joints is helpful for seismic resistance of the structure. Most Tibetan ancient timber structures are suffering from different types of damage to certain extent which is vulnerable to seismic actions. Typical damage problems of the structural components are summarized and the main causes of this damage are analyzed. Different rehabilitation methods that can be implemented are discussed, providing references for maintenance of the structures.